Women Writing Greece: Essays on Hellenism, Orientalism and Travel - Kolocotroni, Vassiliki; Mitsi, Efterpi (Rodopi, 2008)
Women Writing Greece explores images of modern Greece by women who experienced the country as travellers, writers, and scholars, or who journeyed there through the imagination. The essays assembled here consider women's travel narratives, memoirs and novels, ranging from the eighteenth to the late twentieth century, focusing on the role of gender in travel and cross-cultural mediation and challenging stereotypical views of 'the Greek journey', traditionally seen as an antiquarian or Byronic pursuit. This collection aims to cast new light on women's participation in the discourses of Hellenism and Orientalism, examining their ideological rendering of Greece as at once a luminous land and a site crossed by contradictory cultural memories. Arranged chronologically, the essays discuss encounters with Greece by, among others, Lady Elizabeth Craven, Lady Hester Stanhope, Lady Montagu, Lady Morgan, Mary Shelley, Felicia Skene, Emily Pfeiffer, Eva Palmer, Jane Ellen Harrison, Virginia Woolf, Ethel Smyth, Christa Wolf, Penelope Storace and Gillian Bouras, and analyse them through a variety of critical, historical, contextual and theoretical frames.